Determinants of reinsurance costs for Turkish non-life insurance companies - AVCI, EMİN (My University, 2022)
Purpose- Reinsurance is one of the most common practices in the insurance sector, however, it is not free of charge. The insurance companies have to bear some costs to assure the reinsurers for sharing the risks of potential losses. The objective of this article is to explore the firm-level factors that may affect the cost of reinsurance to an insurance company. In order to achieve the objective, the relationship between reinsurance cost and financial and technical ratios, which are good monitoring tools for insurance companies, has been analyzed. Methodology- The relationship between reinsurance cost and financial and technical ratios has been analyzed using panel data analyses. The data was obtained from the official website of the Insurance Association of Türkiye (IAT). The data set include variables for 26 non-life companies for the period of 2009 - 2021. Two separate models have been developed; one model with financial ratios and the second model with technical ratios. The analyses are also repeated by uncovering the COVID-19 period and the 2018 currency crisis. Findings- The findings of the study revealed that the financial ratios, namely return on assets and debt ratio; technical ratio as retention ratio all have a negative significant effect on reinsurance cost. That is the higher the profit, debt level, and retention ratio, the more reluctant the insurance companies are to bear insurance costs and carry most of the risks. Such variables have a negative effect on reinsurance costs with a higher significance level, even after uncovering the recent COVID-19 pandemic and 2018 currency crisis periods. When COVID-19 and 2018 currency crisis periods are excluded from the data set, Net Combined Ratio becomes an additional significant factor affecting the reinsurance costs. Conclusion- As long as there is an insurance sector, there must be a reinsurance sector alongside. Companies from both sectors need to go hand in hand in order to eliminate the possible future severe damages in case of fire, flood, or earthquake. However, reinsuring an insurance contract would generate costs like every transaction in this economic system. The findings indicate that determinants of reinsurance cost are as follow; return on asset, debt ratio, and retention ratio. This result would help management teams of insurance companies foresee the cost of reinsurance when they monitor closely the ratios. In other words, the management team of an insurance company could control and handle the condition of reinsurance contracts that generate cost.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Reinsurance cost; insurance; firm performance; panel data analysis; ratio analysis.